Effects of thermal aging on the performance of ordinary and novel superhydrophobic and oleophobic ultra-fine dry powder extinguishing agent - Yurong Liu; Ruiyu Chen; Wang Zhixuan; Rui Zhang; Hongling Jing; Daheng Yu; Renming Pan (Scientific Reports)
Abstract Powder-based fire extinguishing agents have become a kind of promising substitutes for halon extinguishing agents in civil aircrafts. However, their storage lifespan, significantly influenced by the thermal aging, emerges as a crucial yet overlooked aspect for aviation use. This study investigates the effects of thermal aging cycles on various parameters of ordinary dry powder extinguishing agent (ODPEA) and novel superhydrophobic and oleophobic ultra-fine dry powder extinguishing agent (SHOU DPEA), including surface microscopic morphology, D90 (the diameter at which 90% of the cumulative volume of particles are equal to or smaller than this value), chemical structure, hydrophobic and oleophobic angles, flowability, extinguishing time and effectiveness. The results indicate that SHOU DPEA exhibits smaller particle size, more regular particle shape, significantly superior heat stability and flowability compared to ODPEA. Furthermore, the D90 value evolution of ODPEA with aging time exhibits two stages: (a) a slow and linear growth stage (0–160 days), and (b) a rapid and substantial growth stage (160–200 days). However, SHOU DPEA shows a gradual increase in D90 value throughout the entire accelerated aging process. After 160 days of aging or more, the performance of ODPEA has significantly deteriorated, while SHOU DPEA has shown less degradation. Specially, the extinguishing concentration for the 160-day-aged ODPEA exceeds that of non-aged ODPEA by 10%, whereas the concentration of the 200-day-aged SHOU DPEA is less than 10% of the non-aged counterpart. Additionally, the predicted lifespans for ODPEA and SHOU DPEA at room temperature (25 °C) are 2715 days and over 4525 days, respectively. These findings can provide valuable guidance for assessments and the selection of aviation fire extinguishing agents.